Smart hand sanitizer dispenser - Zainudin, Zafirah Izni Binti; San, Low Yee; Abdulla, Raed (Journal of Applied Technology and Innovation, 2022)
The main aim of this research is to design a smart hand sanitizer dispenser that dispenses the optimum amount of sanitizer based on palm image processing with enhanced IoT features. The research problem of this project is that hand sanitizer dispensers are mostly provided in manual form. This will make the hand sanitizer dispenser contaminated. The usage of the hand sanitizer is also controlled by individual behaviors. They may use it very little, which will not achieve the purpose of using it to curb infectious viruses. They may also use it too much and it can be wasted. The method used to achieve the objectives of this project is by using the Raspberry Pi B+. The system is implemented by using Haar Cascade Classifier to detect the hand palm and measure the hand by using Euclidean distance and pixels per metric. The system also consists of monitoring and alert features. The liquid level of the hand sanitizer is monitored using Node-RED. An alert system is also constructed to remind the owner to refill the hand sanitizer. Other than that, a PIR sensor is used to detect the presence of a human nearby and give out a message through a speaker to remind people to use the hand sanitizer.